Transcriptome-wide identification and expression profiles of the WRKY transcription factor family in Broomcorn millet (Panicum miliaceum L.). (December 2016) - Yue, Hong; Wang, Meng; Liu, Siyan; Du, Xianghong; Song, Weining; Nie, Xiaojun
Abstract Background WRKY genes, as the most pivotal transcription factors in plants, play the indispensable roles in regulating various physiological processes, including plant growth and development as well as in response to stresses. Broomcorn millet is one of the most important crops in drought areas worldwide. However, the WRKY gene family in broomcorn millet remains unknown. Results A total of 32 PmWRKY genes were identified in this study using computational prediction method. Structural analysis found that PmWRKY proteins contained a highly conserved motif WRKYGQK and two common variant motifs, namely WRKYGKK and WRKYGEK. Phylogenetic analysis of PmWRKYs together with the homologous genes from the representative species could classify them into three groups, with the number of 1, 15, and 16, respectively. Finally, the transcriptional profiles of these 32 PmWRKY genes in various tissues or under different abiotic stresses were systematically investigated using qRT-PCR analysis. Results showed that the expression level of 22 PmWRKY genes varied significantly under one or more abiotic stress treatments, which could be defined as abiotic stress-responsive genes. Conclusions This was the first study to identify the organization and transcriptional profiles of PmWRKY genes, which not only facilitates the functional analysis of the PmWRKY genes, and also lays the foundation to reveal the molecular mechanism of stress tolerance in this important crop.